Night gallery. Season three [videorecording (DVD)] - Serling, Rod, 1924-1975; Bixby, Bill, 1934-1993; Field, Sally; Dee, Sandra; Nimoy, Leonard; Rooney, Mickey; Price, Vincent, 1911-1993 (2012)
Join master of mystery Rod Serling (The Twilight Zone) as he invites you into the transfixing world of fantasy, horror and science fiction. In its third and final season, Serling once again presents stories that still leave an undeniable chill, filled with restless spirits, murderous spouses and unidentified terrors that go bump in the night.